2022
DOI: 10.31557/apjcp.2022.23.8.2779
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Value of Claudin-4 and EZH2 Immunohistochemistry in Effusion Cytology

Abstract: some cases, morphologic distinction between MAC and reactive mesothelial cells (RMC) is challenging, as both may show wide range of morphologic variations, or only few suspicious cells might be seen (Ikeda et al., 2011). In such doubtful cases, application of immunohistochemical markers to cell blocks allows more precise diagnosis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(62 reference statements)
2
1
0
Order By: Relevance
“…It is a highly useful marker for distinguishing reactive mesothelial cells and metastatic adenocarcinoma. Several previous studies have analysed the sensitivity and specificity of claudin‐4 in the evaluation of effusion cytology (Table 3) with most studies highlighting the 100% sensitivity for adenocarcinomas irrespective of primary site as was observed in the present study as well 4,6,7,11–15 . However, there are some discrepancies with regards to the specificity.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It is a highly useful marker for distinguishing reactive mesothelial cells and metastatic adenocarcinoma. Several previous studies have analysed the sensitivity and specificity of claudin‐4 in the evaluation of effusion cytology (Table 3) with most studies highlighting the 100% sensitivity for adenocarcinomas irrespective of primary site as was observed in the present study as well 4,6,7,11–15 . However, there are some discrepancies with regards to the specificity.…”
Section: Discussionsupporting
confidence: 48%
“…with most studies highlighting the 100% sensitivity for adenocarcinomas irrespective of primary site as was observed in the present study as well. 4,6,7,[11][12][13][14][15] However, there are some discrepancies with regards to the specificity. Although the clone 3EC21 has been used in all the studies, some studies have reported lower specificity of 70%-77%.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the sensitivity, specificity, positive predictive, and negative predictive values for CLDN4 in metastatic adenocarcinoma were 85%, 100%, 100%, and 75%, respectively [158]. Similar results were noted by Elhosainy et al, where CLDN4 exhibited 95.8% sensitivity and 96.9% specificity in the detection of metastatic adenocarcinoma [159].…”
Section: Tumor Markerssupporting
confidence: 81%